Pemilihan Pembelanjaan Online Dengan Metode Fuzzy Multiple Atrribute Decision Making - Rima Aprilia (Universitas Islam Raden Rahmat, Malang, 2023)
E-commerce (online retail) is a technology that is used by modern society today to transact or carry out the buying and selling process on the internet. This online shopping trend is supported by an increasing number of online shopping platforms to choose from based on criteria such as price of goods, completeness of goods, shipping costs, quality of goods, and length of delivery time. With a smartphone, this online shopping selection becomes an alternative for the shopping process that saves time and energy. Fuzzy Multiple Attribute Decision Making can be applied to the selection of online shopping by combining the Simple Additive Weight method to get the ranking results from the most appropriate e-commerce to choose shopping based on criteria. The formulation can be applied to everyday life and become a reference for alternative choices for online shopping.